Identification of bacteria and fungi responsible for litter decomposition in desert steppes via combined DNA stable isotope probing - Ye, He; Tu, Nare; Wu, Zhendan; He, Shilong; Zhao, Yu; Yue, Mei; Hong, Mei (Frontiers in Microbiology, 2024)
Introduction Soil microorganisms play crucial roles in determining the fate of litter in desert steppes because their activities constitute a major component of the global carbon (C) cycle. Human activities lead to increased ecosystem nitrogen (N) deposition, which has unpredictable impacts on soil microorganism diversity and functions. Nowadays, it is necessary to further study the succession of these microorganisms in the process of litter decomposition in desert steppe, and explore the effect of N deposition on this process. This issue is particularly important to resolve because it contributes to the broader understanding of nutrient cycling processes in desert steppes. Methods In this study, DNA stable isotope probing (DNA-SIP) was used to study changes in soil bacterial and fungal community composition and function during 8 weeks of culture of 13C-labeled litter in desert steppes. Results The results were as follows: (1) Actinomycetota, Pseudomonadota, and Ascomycota are the main microorganisms involved in litter decomposition in desert steppes; (2) N deposition (50 kg ha−1 year−1) significantly increased the relative abundance of some microorganisms involved in the decomposition process; and (3) N deposition likely promotes litter decomposition in desert steppes by increasing the abundances of N cycles bacteria (usually carrying GH family functional genes). Discussion These findings contribute to a deeper understanding of the C assimilation mechanisms associated with litter residue production, emphasizing the importance of extensive C utilization.